Patterns in abundance and size of sharks in northwestern Australia: cause for optimism. (10th October 2019) - Braccini, Matias; Molony, Brett; Blay, Nick
Abstract: Reliable information for population assessments is rare for sharks. We quantified patterns in catch rates and mean size for numerous tropical and subtropical species from 15 years of fishery-independent surveys (2002–2017) in northwestern Australia. This study region represents an area of 0.8 million km 2 which was closed to commercial shark fishing from 1993 or 2005 onward due to the very high State-wide catches of sandbar ( Carcharhinus plumbeus ) and dusky ( Carcharhinus obscurus ) sharks. A total of 43 shark and ray species were sampled, with sandbar shark being the most commonly caught species, followed by milk ( Rhizoprionodon acutus ), spot-tail ( Carcharhinus sorrah ), tiger ( Galeocerdo cuvier ), blacktip ( Carcharhinus limbatus and Carcharhinus tilstoni ), dusky and sliteye ( Loxodon macrorhinus ) sharks, and scalloped hammerhead ( Sphyrna lewini ). For sandbar shark, catch rates increased between 2008 and 2017 whereas for other taxa catch rates were mostly stable (albeit fluctuating). Mean size at capture fluctuated across years with no particular trends. Unlike for other parts of the world, catch rates and mean size of northwestern Australian sharks have been stable or increased in recent years. Though most shark species have conservative life histories, when science, management and enforcement work synergistically, sustainable resource use, recovery and conservation outcomes can all be achieved.